Actinidia spp. (Kiwifruit): A Comprehensive Review of Its Nutraceutical Potential in Disease Mitigation and Health Enhancement - Allah Rakha; Nida Rehman; Rimsha Anwar; Hina Rasheed; Roshina Rabail; Zuhaib F. Bhat; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Frontiers)
ABSTRACT This review offers an in‐depth exploration of the Actinidia species (kiwifruit) nutritional composition, the pivotal role of its primary bioactive compounds, and their potential applications across the aforementioned health concerns. Furthermore, this article sheds light on kiwifruit allergies, providing valuable insights for readers. Kiwifruit, particularly the varieties “Actinidia chinensis var. chinensis,” “A. chinensis var. deliciosa,” and Actinidia arguta, are an exceptional source of polyphenolic compounds like flavonoids, stilbenoids, and phenolic acids. This distinctive phytochemical profile endows kiwifruit with promising nutraceutical potential against various diseases. These bioactive compounds are pivotal in preventing or delaying the onset of multiple health conditions and protecting the body from endogenous oxidative damage. Recent research has unveiled the fruit's remarkable attributes, such as hypolipidemic, antidiabetic, antihypertensive, anticancer, antiobesity, and antiplatelet aggregation properties. Additionally, kiwifruit effectively safeguards against hepatotoxicity, nephrotoxicity, neuropathy, and neurological disorders. Nevertheless, it is worth noting that kiwifruit consumption may induce allergies due to 13 IgE‐reactive compounds. They are proteins and glycoproteins with molecular masses ranging from 10 to 51 kDa. The primary allergen in kiwifruit is a cysteine protease known as Act d 1, which accounts for 50% of the soluble protein extract. Kiwifruit's burgeoning potential for preventing and treating various diseases has captured the attention of numerous researchers. However, further advanced research is warranted, particularly in neurodegenerative, hepatic, and renal disorders. Continued investigation promises to unveil even more remarkable aspects of kiwifruit's contributions to human health.